Ethyl acetate extract and its major constituent, isorhamnetin 3‐O‐rutinoside, from Nitraria retusa leaves, promote apoptosis of human myelogenous erythroleukaemia cells - Boubaker, J. (Cell Prolif, 2011)
Objective:  Fractionation of ethyl acetate extract (EA) obtained from Nitraria retusa leaves was assessed using different methods of chromatography, and isorhamnetin3‐O‐rutinoside (I3‐O‐R) was isolated from this extract. Its structure was determined using data obtained from (1)H and (13)C NMR spectra, as well as by various correlation experiments (COSY, HMQC and HMBC). Both EA extract and I3‐O‐R were investigated for their ability to induce apoptosis in human chronic myelogenous erythroleukaemia cells (K562). Materials and methods:  Apoptosis of cells from the K562 line was detected by DNA fragmentation, PARP cleavage and by evaluating activities of caspases 3 and 8. Results:  Apoptosis, revealed by DNA fragmentation and PARP cleavage, was observed after 48‐h incubation of these human myelogenous erythroleukaemia cells (K562), with the tested products. Likewise, caspase 3 and caspase 8 activities were induced in the presence of the EA extract and I3‐O‐R after 48 h of incubation. Conclusion:  Our results strongly suggest the involvement of the extrinsic pathway of apoptosis in cells treated by both the original EA extract and its major component, I3‐O‐R.